2017
DOI: 10.1590/1807-1929/agriambi.v21n10p675-680
|View full text |Cite
|
Sign up to set email alerts
|

Production and antioxidative metabolism in bell pepper grown with saline water in hydroponic system

Abstract: A B S T R A C TThis study aimed to evaluate the effect of salt stress on production and antioxidative defense metabolism of two bell pepper cultivars (Capsicum annuum L.) grown hydroponically. The experimental design was in randomized blocks, with treatments arranged in a 5 x 2 factorial scheme with five replicates. The treatments consisted of five salinity levels of the nutrient solution (2.0, 3.5, 4.5, 5.5 and 6.5 dS m -1 ) with two bell pepper cultivars, 'Bruno' and 'Rúbia' . Biomass and yield were reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
1
3
0
Order By: Relevance
“…These results agreed with those reported by various authors who studied the bell pepper crop under saline stress conditions, cultivated in either soil (Leonardo et al, 2007;Lima et al, 2016) or substrate (Arruda et al, 2011;Rubio et al, 2011;Nunes et al, 2013;Furtado et al, 2017;Lima et al, 2017). Reductions in fruit size and weight due to saline stress and, consequently, in the economic performance of the crop, are caused by physiological and biochemical changes in the cells or at the molecular level (Munns & Tester, 2008).…”
Section: F1 F2 F3 F4 F5supporting
confidence: 90%
See 1 more Smart Citation
“…These results agreed with those reported by various authors who studied the bell pepper crop under saline stress conditions, cultivated in either soil (Leonardo et al, 2007;Lima et al, 2016) or substrate (Arruda et al, 2011;Rubio et al, 2011;Nunes et al, 2013;Furtado et al, 2017;Lima et al, 2017). Reductions in fruit size and weight due to saline stress and, consequently, in the economic performance of the crop, are caused by physiological and biochemical changes in the cells or at the molecular level (Munns & Tester, 2008).…”
Section: F1 F2 F3 F4 F5supporting
confidence: 90%
“…In bell peppers, saline stress causes a reduction in photosynthetic activity, photosynthesis, transpiration, stomatal conductance, gas exchange and photosystem II efficiency, culminating in yield losses (Lima, Morais, Silva, Camara, & Willadino, 2017;Nunes, Dias, Moura, Souza Neto, & Costa, 2013;Amirinejad, Sayyari, Ghanbari, & Kordi, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…CAT activity increased in Hail 548, with a maximum increase close to 7.6% when treated with 75 mM NaCl. The increase in CAT activity favors the elimination of H 2 O 2 , both generated by SOD and produced in photorespiration [ 53 ]. Abdelaal et al [ 23 ] found that in sweet pepper, an increase in malondialdehyde (MDA) content under the salinity condition and the antioxidants SOD and CAT activities increased salt stress and were higher in the tolerant cultivar.…”
Section: Discussionmentioning
confidence: 99%
“…pigments apparently involved in the protection against photoinhibition(Freire et al, 2013) Lima et al (2017). observed a linear reduction in the contents of Cl b and Cl T in bell pepper plants by increasing the salinity of…”
mentioning
confidence: 99%